Advanced placement course credit and undergraduate student success in gateway science courses. Issue 2 (23rd July 2022) - Fischer, Christian; Witherspoon, Eben; Nguyen, Ha; Feng, Yanan; Fiorini, Stefano; Vincent‐Ruz, Paulette; Mead, Chris; Bork Rodriguez, William Nicholas; Matz, Rebecca L.; Schunn, Christian
Abstract: Approximately 2 million students take Advanced Placement (AP) examinations annually. However, departmental policies that allow students to replace introductory courses with AP credit greatly vary within and across universities, even across relatively similar universities. This study examines the impact of AP credit policies on second‐course success in introductory Biology, Chemistry, and Physics course sequences at six large public research universities ( N = 48, 230 students). Applying logistic regression analyses, we found that general performance indicators and measures of systemic inequities during high school were predictive of students earning skip‐eligible scores. Interestingly, we descriptively discovered wide variation across institutions and disciplines in the percentage of students who chose to skip when meeting their local policies. However, logistic regression analysis did not find general trends of inequalities for skipping courses for students with skip‐eligible scores. We then applied inverse‐probability weights with regression adjustment to examine the effects of course skipping. We found that students who skipped their first course with AP credit actually performed similarly well or better in subsequent courses than did students who did not skip, even in contexts where lower AP scores were accepted. Therefore, our study suggests administrators to increase coherence in AP credit policies across departments and disciplines. In particular, we encourage modifying AP credit policies and academic advising to encourage students to skip when they have eligible AP scores. Benefits may include reductions in unnecessary coursework that is burdensome for both students and universities, potentially freeing up resources to better support students who were not privileged to enroll in AP courses during their high school education.